Macromol. Chem. Phys. 2/2018. Issue 2 (19th January 2018) - Imre, Balazs; Gojzewski, Hubert; Check, Casey; Chartoff, Richard; Vancso, G. Julius
Abstract : Front Cover : Atomic force microscopy topography (1 × 1 μm) and modulus map (125 × 125 nm) images reveal the rod‐like morphology of hard domains in polycaprolactone‐based segmented polyurethanes. The corresponding structural model shows these domains as parallel stacks of hard segments embedded in a soft polycaprolactone matrix. Further details can be found in article number1700214 by Richard Chartoff* and co‐workers.